(untitled) (Revista Argentina de Musicología, 2022)
The article studies the articulation of the world of hip-hop in Santiago of Chile during the decade of 1980 and 1990 from a reading about a use of the casete that transcended the mere listening to music. We show the relevance of this technological object for the consumption of a foreign type of music that was difficult to access in relation to a certain socioeconomic profile, together with the possibility of creating beats (rap musical bases), registering and distributing music, and even it’s use to play live music. To understand this articulation, we conceive the casete as a meta-device for it’s ability to have multiple uses and functions. Methodologically, the research was based on the analysis of various documents and semi-structured interviews with those who made rap in Santiago during the established period.